Pemberian Ekstrak Oncom Hitam dan Merah Memperpanjang Siklus Estrus dan Mempertebal Endometrium Tikus Putih - Aini, Hanifah Alshofa Nurul; Laksmi, Desak Nyoman Dewi Indira; Setiasih, Ni Luh Eka; Purbantoro, Steven Dwi (Jurnal Veteriner; Vol 21 No 4 (2020)DO - 10.19087/jveteriner.2020.21.4.565, 2020)
hytoestrogens are active compounds, derived from plants, which have a similar structure and function as estrogen. Phytoestrogens are commonly found in legumes. Oncom, which is assumed containing phytoestrogens, is one of the most famous legumes food from Indonesia and widely consumed daily in West Java. This study was aimed to determine the effect of oncom extract on estrous cycle, endometrium thickness, and the number of antral follicles in productive age rats ( Rattus novergicus ). This experimental study was using 21 three-to-four-month-old fertile female rats and divided into three groups. Group I (K) was considered    as a control group without any treatment. Group II and III were treatment groups which were given black (H) and red (M) oncom extracts 0.005 g/g body weight, respectively, orally with a feeding tube for 14 days. The length of the estrous cycle was measured by performing vaginal swab with interval 12 hours after first treatment was given and during the treatment. Endometrium thickness and the number of antral follicles were measured by collecting the organs uterus and ovary for histological purpose with paraffin method after rats were euthanized post-treatment oncom extracts for 14 days. Data were analyzed by ANOVA and continued with LSD test. The total length of estrous cycle of control group, black oncom extract group, and red oncom extract group was 107,43±3,16 hours, 141,43±15,36 hours, and 161,14±17,10 hours, respectively. The mean of endometrium thickness of control group, black oncom extract group, and red oncom extract group was 346,945±65,88 ?m, 485,740±86,69 ?m, and 533,904±78,93 ?m, respectively. The number of antral follicles of control group, black oncom extract group, and red oncom extract group was 6,00±1,54, 8,43±2,99, and 9,14±2,72, respectively. Results showed that black and red oncom extracts had a significant effect on the length of estrous cycle and endometrium thickness in rats, yet there is no significant difference in the number of antral follicles. In summary, black and red oncom extracts had effects on the length of estrous cycle and endometrium thickness, yet there was no effect on the number of antral follicles.